Pubo-Femoral Distances Measured Reliably by Midwives in Hip Dysplasia Ultrasound - Hans-Christen Husum; Michel Bach Hellfritzsch; Rikke Damkjær Maimburg; Mads Henriksen; Natallia Lapitskaya; Bjarne Møller-Madsen; Ole Rahbek (MDPI AG, 2022)
The pubo-femoral distance (PFD) has been suggested as an ultrasound screening tool for developmental dysplasia of the hip (DDH). The aim of this study was to examine if midwives undergoing minimal training could reliably perform pediatric hip ultrasound and PFD measurements. Eight recruited midwives performed two rounds of independent blinded PFD measurements on 15 static ultrasound images and participated in four supervised live-scanning sessions. The midwives were compared to a group of three experienced musculoskeletal radiologists. Reliability was evaluated using inter-rater correlation coefficients (ICC). Linear regression was used to quantify the learning curve of the midwives as a group. There was near complete intra- and inter-rater agreement (ICC > 0.89) on static ultrasound images across both rounds of rating for midwives and radiologists. The midwives performed a mean of 29 live hip scans (range 24-35). The mean difference between midwives and supervising radiologists was 0.36 mm, 95% CI (0.12-0.61) for the first session, which decreased to 0.20 mm, 95% CI (0.04-0.37) in the fourth session. ICC for PFD measurements increased from 0.59 mm, 95% CI (0.37-0.75) to 0.78 mm, 95% CI (0.66-0.86) with progression in sessions. We conclude that midwives reliably perform PFD measurements of pediatric hips with minimal training.